Ethiopia unbound : studies in race emancipation - Hayford, J. E. Casely (Joseph Ephraim Casely), 1866-1930. (London : Cass, 1969)
One of the first novels in English by an African. It has been cited as the earliest pan-African fiction. The novel is set in both Africa and England. It relies on philosophical debates between an African and his English friend, as well as references to contemporary African events and ancient African history, to provide a context for its exploration of African identity and the struggle for emancipation.
Includes bibliographical references.
Keywords: 1900-1999; Friendship -- Fiction; Ghanaian fiction (English) -- 20th century; Friendship; African fiction (English); Nationalism -- Africa -- Fiction; Africa -- Fiction; Africa; Fiction